Analysis of urban water quality trends for effective reservoir sedimentation management in Cameron Highland - Noh N.M.; Sidek L.M.; Haron S.H.; Puad A.H.M.; Selamat Z.; Razad A.Z.A.; Fai C.M. (Inderscience Publishers, 2023)
Agricultural robots; Agriculture; Phosphorus; Reservoir management; Reservoirs (water); Sediment transport; Sedimentation; Water pollution; Water quality; Agricultural activities; Agricultural areas; Agricultural management practice; Effective reservoir; Phosphorus loads; Total phosphorus; Urban water qualities; Water quality indexes; Quality control; agricultural management; agriculture; human activity; index method; reservoir; sedimentation; trend analysis; urban area; water pollution; water quality; Cameron Highlands; Malaysia; Pahang; West Malaysia